Synergistic smart morphing aileron: Experimental quasi-static performance characterization. (July 2015) - Pankonien, Alexander M; Faria, Cassio T; Inman, Daniel J
This article describes the development and characterization of the synergistic smart morphing aileron concept, which leverages the properties of two different smart material actuators to achieve performance that exceeds that of the constituent materials. Utilizing the relatively higher work density and phase transformation of shape memory alloys combined with the larger bandwidth and conformal bending of bonded piezoelectric macro-fiber composites, the resultant synergistic morphing design improves the range of static tip deflections, enabling the capability to hold more trim positions over long timescales while still quickly compensating for dynamic loading. By commanding an input of full-range square waves of 0.01–10 Hz to the actuators, first-order time responses were measured and characterized using a common methodology by tracking a relative time constant. Using this method, aeroelastic effects for each actuator and the combined system were characterized in a wind tunnel at 0° angle of attack with flow speeds ranging from 0 to 15 m/s. This novel approach characterized a large-deflection morphing actuation system with multiple smart materials operating over different timescales. The combined system achieved additive amplitude while tracking the faster actuation response of the macro-fiber composite between 0.1 and 1 Hz.